MODEL INTEGRATIF ANALISIS DATA EVALUASI PENDIDIKAN BERBASIS STATISTIK DESKRIPTIF, ANALISIS TEMATIK, DAN OBSERVASI KELAS DI SMP PLUS AR RAHMAT - Ita Juwita Muhamad; Mulyawan Safwandy (STKIP Subang, 2026)
Effective educational evaluation requires an analytic model that connects measurable outcomes with the learning processes that produce them. This study refined an integrative model of educational evaluation data analysis by combining descriptive statistics, thematic qualitative analysis, and classroom observation. The study used a conceptual review supported by field data from an IPS lesson in class 8B of SMP Plus Ar Rahmat on 27 April 2026. Quantitative data were collected through an observation rubric, attendance records, participation counts, and academic ledger documentation, while qualitative data were obtained from classroom field notes. The synchronized observation score was 41 out of 88, or 46.59 percent, and was categorized as sufficient. Active participation was low, with only 3 of 17 students asking questions, or 17.65 percent. The academic ledger showed relatively strong IPS achievement, with scores ranging from 84 to 89 and a mean of 87.63. Thematic analysis identified five themes: limited participation, less conducive classroom conditions, complex material without adequate media, interrupted instructional focus, and strong student manners.